SERIAL EDUKASI KELUARGA SEHAT: UPAYA PENCEGAHAN PENYAKIT PNEUMONIA PADA ANAK BALITA - Al Widad , Alfaniah Aufa Shidqi; Novendy, Novendy; Sherlyna, Feby; Lonan, Cantika Monica Eleanor Mutiara; Almahdin, Masali (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Pneumonia is one of the leading causes of death among children worldwide. Each year, approximately 700,000 children under the age of five die from this disease—equivalent to around 2,000 child deaths per day, or one child every 45 seconds. In Indonesia, the incidence of pneumonia in children has also been increasing annually. Data from Puskesmas Legok recorded 208 cases of pneumonia throughout 2024, with 124 cases (59.6%) occurring in children under five. A mini survey conducted in February 2025 at the same health center revealed that approximately 80% of the community still lacks sufficient knowledge about childhood pneumonia. Based on these findings, a medical outreach team from the Faculty of Medicine at Universitas Tarumanagara organized an educational program to raise awareness about pneumonia in children within the local community. The activity involved direct health education and awareness sessions for residents. The effectiveness of this initiative was evaluated by comparing the participants' knowledge before and after the session, using pre- and post-tests. A total of 24 participants took part in this health outreach activity. The average pre-test score was 76.7 points, while the post-test average increased to 90.3 points, indicating an 18% improvement. This health outreach program successfully enhanced participants’ understanding of childhood pneumonia. It is hoped that this increased awareness will also lead to earlier recognition of pneumonia symptoms by parents, allowing children to receive prompt medical attention and avoid potentially serious complications.